Abatement of 2, 4-D by H2O2 solar photolysis and solar photo-Fenton-like process with minute Fe(III) concentrations. (1st November 2018) - Serra-Clusellas, Anna; De Angelis, Laura; Lin, Chung-Ho; Vo, Phuc; Bayati, Mohamed; Sumner, Lloyd; Lei, Zhentian; Amaral, Nathalia B.; Bertini, Liliana M.; Mazza, Jose; Pizzio, Luis R.; Stripeikis, Jorge D.; et al.
Abstract: The Photo-Fenton-like (PF-like) process with minute Fe(III) concentrations and the Hydrogen Peroxide Photolysis (HPP), using Xe-lamp or solar light as sources of irradiation, were efficiently applied to eliminate the herbicide 2, 4-D from water. PF-like experiments concerning ferric and H2 O2 concentrations of 0.6 mg L −1 and 20 mg L −1 respectively, using Xenon lamps (Xe-lamps) as a source of irradiation and 2, 4-D concentrations of 10 mg L −1 at pH 3.6, exhibited complete 2, 4-D degradation and 77% dissolved organic carbon (DOC) removal after 30 min and 6 h of irradiation respectively whereas HPP (in absence of ferric ions) experiments showed a 2, 4-D reduction and DOC removal of 90% and 7% respectively after 6 h of irradiation. At pH 7.0, HPP process achieved a 2, 4-D abatement of approximately 75% and a DOC removal of 4% after 6 h. PF-like exhibited slightly improved 2, 4-D and DOC removals (80% and 12% respectively) after the same irradiation time probably due to the low pH reduction (from 7.0 to 5.6). Several chlorinated-aromatic intermediates were identified by HPLC-MS. These by-products were efficiently removed by PF at pH 3.6, whereas at neutral PF-like and acid or neutral HPP, they were not efficiently degraded. With natural solar light irradiation, 10 and 1 mg L −1 of 2, 4-D were abated using minor H2 O2 concentrations (3, 6, 10 and 20 mg L −1 ) and iron at 0.6 mg L −1 in Milli-Q water. Similar results to Xe-lamp experiments were obtained, where solar UV-B + A light H2 O2 photolysis (HPSP) and solar photo-Fenton-like (SPF-like) played an important role and even at low H2 O2 and ferric concentrations of 3 and 0.6 mg L −1 respectively, 2, 4-D was efficiently removed at pH 3.6. Simulated surface water at pH 3.6 containing 1 mg L −1 2, 4-D, 20 mg L −1 H2 O2 and 0.6 mg L −1 Fe(III) under natural sunlight irradiation efficiently removed the herbicide and its main metabolite 2, 4-DCP after 30 min of treatment while at neutral pH, 40% of herbicide degradation was achieved. In the case of very low iron concentrations (0.05 mg L −1 ) at acid pH, 150 min of solar treatment was required to remove 2, 4-D. Graphical abstract: Image 1 Highlights: Photo-Fenton processes at low iron concentrations achieved 2, 4-D degradation. UV-B H2 O2 photolysis was also able to degrade the herbicide 2, 4-D at pH 7 and 3.6 Photo-Fenton process was more effective at acid pH values. Chlorinated-aromatic metabolites were found during photo-induced processes. UV-B H2 O2 photolysis and neutral photo-Fenton led to the low 2, 4-D removal.